(untitled) (International Conference on Computers in Education, 2016)
Massive Open Online Courses (MOOCs) are a rapidly growing form of educational technology and have the potential to deliver world class education. The potential benefits are particularly of paramount importance in developing countries such as India due to paucity of good faculty with regards to scaling up of professional education. India has now officially jumped into the open online courses bandwagon with the government announcing many initiatives with an objective of providing affordable and quality education to all desirous. IITBombayX is one such online platform which offers interactive online classes and MOOCs for faculty professional development. This paper reports findings from MOOC on ET601Tx that were instrumental in 98.6% course completion rate conducted at our institute against a general 24% for this course at all over India. Out of the 146 registered, 144 went on to complete the entire course and received honor code certificates. The post MOOC survey of 133 participants revealed that ‘Institutional Leadership’ in the form of Coordinated Faculty Professional Development Activity (CFPDA) was a major contributing factor in making the faculty persists throughout the course and completing it successfully. The CFPDA at the institution, in the form of review meetings facilitation by education technology mentors, department coordinators has led to 98.6 % persistence and higher scores obtained by the faculty participants.